Assessment of Perceived Risks of Breast Cancer and Breast Cancer Screening Among Women in Five Selected Local Governments in Ogun State, Nigeria. (April 2019) - Allo, T. A.; Edewor, P. A.; Imhonopi, D.
This study examined the perceived risks of breast cancer (BC) and its influence on the BC screening behavior of 992 women residing in rural, urban, and semi-urban communities in five randomly selected local government areas (LGAs) in Ogun State, Nigeria. The article attempts to examine women's perception of BC risk and how this may influence their behavioral disposition to breast screening. Cross-sectional survey and in-depth interviews were utilized to elicit quantitative and qualitative data from respondents. It was found that, although a positive association exists between risk perception of BC and BC screening attendance (β = .411), the association is not statistically significant: p = .204, 95% CI = [0.800, 2.841]. Women's screening behavior is thus not determined by perceived risks, but are rather determined by religious and socio-cultural beliefs in the study area. The socio-cultural milieu and religious idiosyncrasies of women may be considered when developing interventions to encourage mammography screening.